Visible light photocatalysis of amorphous Cl-Ta2O5−x microspheres for stabilized hydrogen generation - Yu, Xin; Zhao, Jingjing; Huang, Jielin; Zhao, Jiawei; Guo, Yifan; Tang, Yanting; Ma, Xinqi; Li, Zhonghua; Guo, Quanhui; Zhao, Junwei (Journal of colloid and interface science, 2020)
[Display omitted] Harvesting broad spectral absorption and visible light photocatalysis of ultrawide bandgap semiconductors are one of most significative topics in the solar energy conversion and utilization fields. In this work, amorphous Cl-Ta2O5−x microspheres were prepared by facile solvothermal method for stabilized visible light photocatalytic hydrogen generation. The acetone absorbed on the interfaces of Ta2O5 nanoparticles induced the formation of oxygen vacancies, enhanced visible light absorption, and formation of Ta2O5−x microspheres with preferred orientations as well as Cl doping. The Cl-Ta2O5−x microspheres showed typical amorphous characteristics and obvious visible light absorption in comparison to those of commercial Ta2O5. More importantly, the prepared Cl-Ta2O5−x microspheres also showed stabilized visible light photocatalytic hydrogen generation performance in the spectral regions of 400 nm ≤ λ ≤ 600 nm mainly because of the introduction of oxygen vacancy defects and Cl doping, which might significantly expand the application of tantalum oxide semiconductors in the broad spectral photocatalytic water splitting.